A Novel Head-Mounted Navigation Device Based on Vibrotactile Stimulation - Ma, Shimeng; Liu, Peter Xiaoping; Gao, Jinfeng (IEEE transactions on instrumentation and measurement, 2024)
Despite the availability of guide dogs and sticks, visually impaired people still have difficulties in traveling and sometimes may encounter dangers. This article presents a novel head-mounted haptic navigation device, for which vibrotactile stimulation is employed at different locations of the head helmet. A set of different navigation instructions is provided through coding the sequential stimuli to the visually impaired people, assisting them in their daily activities. Experiments show that the frontal and temporal regions of the head are more sensitive to vibrotactile stimuli than the top, and the difference thresholds of vibration duration for different parts of the head were derived. The subject's accuracy and reaction time to navigation direction cues were tested in both indoor and outdoor environments. The results showed that the overall navigation accuracy was around 80%, and the response time was around 1.5 s.